Transmission and pathogenicity of novel reassortants derived from Eurasian avian-like and 2009 pandemic H1N1 influenza viruses in mice and guinea pigs - Kong, Weili; Liu, Qinfang; Sun, Yipeng; Wang, Yu; Gao, Huijie; Liu, Lirong; Qin, Zhihua; He, Qiming; Sun, Honglei; Pu, Juan; Wang, Dayan; Guo, Xin; et al. (Nature Publishing Group, 2016)
Given the present extensive co-circulation in pigs of Eurasian avian-like (EA) swine H1N1 and 2009 pandemic (pdm/09) H1N1 viruses, reassortment between them is highly plausible but largely uncharacterized. Here, experimentally co-infected pigs with a representative EA virus and a pdm/09 virus yielded 55 novel reassortant viruses that could be categorized into 17 genotypes from Gt1 to Gt17 based on segment segregation. Majority of novel reassortants were isolated from the lower respiratory tract. Most of reassortant viruses were more pathogenic and contagious than the parental EA viruses in mice and guinea pigs. The most transmissible reassortant genotypes demonstrated in guinea pigs (Gt2, Gt3, Gt7, Gt10 and Gt13) were also the most lethal in mice. Notably, nearly all these highly virulent reassortants (all except Gt13) were characterized with possession of EA H1 and full complement of pdm/09 ribonucleoprotein genes. Compositionally, we demonstrated that EA H1-222G contributed to virulence by its ability to bind avian-type sialic acid receptors, and that pdm/09 RNP conferred the most robust polymerase activity to reassortants. The present study revealed high reassortment compatibility between EA and pdm/09 viruses in pigs, which could give rise to progeny reassortant viruses with enhanced virulence and transmissibility in mice and guinea pig models.